Animal-Assisted Interventions With Dogs in Special Education—A Systematic Review - Meixner, Jana; Kotrschal, Kurt (Frontiers in Psychology, 2022)
Dogs are becoming increasingly popular in pedagogical settings. Particularly children with special educational needs are believed to benefit from dog-assisted interventions. However, reliable evidence for supporting such claims is still scarce and reports on the effectiveness of this approach are often anecdotal. With our review we aim at evaluating the literature to answer the question, whether dog-assisted interventions in an educational setting can help children with special educational needs to improve and to develop their emotional, social and cognitive skills. Following the PRISMA Guidelines, the literature was systematically searched for experimental studies until February 2021. Eighteen studies were finally included, which varied greatly in type of intervention, outcomes measured, sample sizes and scientific quality, which precluded a formal meta-analysis. Hence, we resorted to a narrative synthesis. Overall, the studies report mixed results in the different functional domains of stress reduction, motivation, social skills, cognitive abilities, reading abilities, social conduct and mental well-being. No study reported any negative effects of the intervention. The most unequivocal evidence comes from studies on dogs’ effects on physiological stress response in challenging situations and on motivation and adherence to instructions, reporting significantly lower levels of cortisol in both children and pedagogues in the presence of dogs, as well as increased motivation to learn and participate. Findings for other outcomes, academic or social, however, remain inconclusive. Data on long-term effects are lacking altogether. Still, this review indicates the potentials of dog-assisted interventions in special pedagogy, particularly towards supporting a calm and trustful social atmosphere.